G529(P) The paediatric short stay unit: the power of data in tackling a 'wicked' problem. (27th April 2015) - Hall, D; Kamal, A; Cleugh, F
Abstract : Context: This improvement project took place within the paediatric short-stay unit (PSSU) of a busy inner-city tertiary referral hospital. The aims were firstly to streamline care pathways of patients using the unit, and secondly, to improve patient's and staff's experiences. Problem: The PSSU, which opened 9 years ago, was designed as an unit for acute paediatric short-stay admissions and a facility to accommodate ambulatory work. It comprises of eight inpatient beds, one clinic room and a waiting/playroom. Since opening, unit activity has grown rapidly, with numerous teams using the facility for a variety of reasons. Rapid-access, surgical pre-assessment and prolonged jaundice clinics were incorporated, and more inpatients were discharged early, to complete ambulatory antibiotic courses facilitated by the unit. There were no robust systems in place to record the unit's type and amount of activity. The 'short stay' identity was progressively lost with the inpatient beds often occupied by long-term chronic patients. Staff morale was low and it was suspected that patient experience was suboptimal due to the significant time spent waiting for clinic rooms to be available. Notes were often missing due to the multiple poorly defined referral routes into the unit. Assessment of problem and analysis of its causes: The problem was brought to the 'Quality Improvement Sprint', an innovative forum in which healthcare professionals teamed up with artists, musicians and designers to use creative thinking to tackle problems within the trust. It became apparent that without information regarding activity and patient journeys through the unit, it would be impossible to identify interventions which would improve function. Intervention: A seven-day data gathering exercise was designed to map the journey of every patient who passed through PSSU. Each child and family completed a patient experience proforma and staff kept daily activity diaries. Activity in the Emergency Department (PED), other inpatients wards and day surgery unit was also collected. Strategy for change: The data clearly showed that the high level of activity on PSSU was unsustainable within its confines. Conversely, activity on the adjacent surgical day unit was much lower, indicating suboptimal use of space and highlighting an opportunity to redesign and improve functionality. Many short-stay patients were admitted to the other wards, whilst longer-stay patients were admitted onto PSSU. Particular breeches in the PED were felt to have been avoidable if short-stay beds had been available. Although patient experience was positive, feedback from the staff emphasised the frustration of working in such a chaotic environment. The information was fed back to the Paediatric Executive Board. Effects of changes: The PSSU is reclaiming it's short-stay status. Nurse-led discharge has been introduced and admission pathways from the PED redesigned to improve patient flow. A 'virtual PSSU' trial is underway on the ward, with ring-fencing of a number of beds to be reserved for short stay patients and to be staffed by PSSU. Relevant workload has been diverted to outpatients and a merger of PSSU and surgical day unit is being considered. Modelling of very short-stay patients suitable for a co-located observation bay, is informing plans for the PED rebuild. Lessons learnt: Initially the 'PSSU problem' seemed too complicated to solve. Working with designers in the QI Sprint allowed us to devise a novel approach to improving the quality of care provided within the PSSU. The data gathering exercise was very powerful and quantified the issues objectively. This enabled us to devise a clear message when disseminating findings and campaigning for change. Mapping individual patient journeys brought a human face to the unit. Message for others: Data is powerful and can help define an 'undefinable' problem.